Developing Teachers’ Team Work Enhance Program Under Khon Kaen Primary Educational Service Area Office 4 - Mungkun, Peerada; Thanapatmeemanee, Hemmin (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study current conditions and desirable conditions of teachers’ team work under Khon Kaen Primary Educational Service Area Office 4, 2) to developing the teachers’ team work enhance program under Khon Kaen Primary Educational Service Area Office 4. This research had 2 phases; Phase 1 to study current conditions and desirable conditions of teachers’ team work under Khon Kaen Primary Educational Service Area Office 4. The samples group consisted of 322 directors and teachers selected by multi-stage sampling. Phase 2to developing the teachers’ team work enhance program under Khon Kaen Primary Educational Service Area Office 4, program assessed by 7 luminaries selected by purposive sampling. Research instrument were questionnaire, interviews and assessment form. The statistics used for analyzing data were percentage, mean and standard deviation. The result of research were found: 1. The current conditions of teachers’ team work under Khon Kaen Primary Educational Service Area Office 4 overall were at high levels and the desirable conditions overall were at highest levels. 2. The teachers’ team work enhance program under Khon Kaen Primary Educational Service Area Office 4 consisted 6 components were as follows 1) The importance of program 2) Program objectives 3) Program structure 4) Development methods 5) Content and essence of the program and 6) Evaluation.